Vascular defects of DYRK1A knockouts are ameliorated by modulating calcium signaling in zebrafish - Hyun-Ju Cho; Jae-Geun Lee; Jong-Hwan Kim; Seon-Young Kim; Yang Hoon Huh; Hyo-Jeong Kim; Kyu-Sun Lee; Kweon Yu; Jeong-Soo Lee (The Company of Biologists, 2019)
DYRK1A is a major causative gene in Down syndrome (DS). Reduced incidence of solid tumors such as neuroblastoma in DS patients and increased vascular anomalies in DS fetuses suggest a potential role of DYRK1A in angiogenic processes, but in vivo evidence is still scarce. Here, we used zebrafish dyrk1aa mutant embryos to understand DYRK1A function in cerebral vasculature formation. Zebrafish dyrk1aa mutants exhibited cerebral hemorrhage and defects in angiogenesis of central arteries in the developing hindbrain. Such phenotypes were rescued by wild-type dyrk1aa mRNA, but not by a kinase-dead form, indicating the importance of DYRK1A kinase activity. Chemical screening using a bioactive small molecule library identified a calcium chelator, EGTA, as one of the hits that most robustly rescued the hemorrhage. Vascular defects of mutants were also rescued by independent modulation of calcium signaling by FK506. Furthermore, the transcriptomic analyses supported the alterations of calcium signaling networks in dyrk1aa mutants. Together, our results suggest that DYRK1A plays an essential role in angiogenesis and in maintenance of the developing cerebral vasculature via regulation of calcium signaling, which may have therapeutic potential for DYRK1A-related vascular diseases.